2016
DOI: 10.18240/ijo.2016.01.26
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic manifestations of celiac disease

Abstract: Celiac disease is an autoimmune disorder that affects the small intestine of genetically predisposed individuals. Ophthalmic manifestations are within the extra-intestinal manifestations, and can be divided into those of autoimmune disorders or those due to absorptive disabilities. This article reviewed the ophthalmologic manifestation of celiac disease. Ophthalmic symptoms are rare, but should be investigated in patients with celiac disease and taken into consideration as the first systemic manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
1
13
1
Order By: Relevance
“…The manifestations related to autoimmune disorders are orbital myositis, uveitis, thyroiditis associated with orbitopathy and brain occipital calcification. [1] Similar presentations of celiac disease with acute loss of vision related optic neuropathy has been reported in literature. Boushehri et al r e p o r t e d a n a d u l t w h o r e s p o n d e d t o immunosuppressive therapy and gluten free diet.…”
supporting
confidence: 71%
“…The manifestations related to autoimmune disorders are orbital myositis, uveitis, thyroiditis associated with orbitopathy and brain occipital calcification. [1] Similar presentations of celiac disease with acute loss of vision related optic neuropathy has been reported in literature. Boushehri et al r e p o r t e d a n a d u l t w h o r e s p o n d e d t o immunosuppressive therapy and gluten free diet.…”
supporting
confidence: 71%
“…Pseudotumor cerebri, malnutrition retinopathy, uveitis, and cataracts are ocular manifestations that can be seen as a result of autoantibody-related systemic inflammation or malnutrition in CD patients. [ 4 ] None of these diseases were found in the current study. In recent years, changes in choroidal thickness,[ 9 10 ] ocular surface and tear film,[ 5 ] anterior chamber features,[ 6 ] and retinal nerve fiber layer thickness[ 6 ] have been the ocular parameter differences reported in CD patients.…”
Section: Discussioncontrasting
confidence: 49%
“…In recent years, ophthalmologists have researched ocular changes in CD patients, which are caused by the extraintestinal involvement characteristic of this autoimmune disease. [ 4 5 6 7 8 9 10 ] Vascular changes and endothelial dysfunction have recently been demonstrated in CD patients. [ 11 ] However, a comprehensive literature review has found no study investigating macular perfusion parameters in CD patients.…”
mentioning
confidence: 99%
“…In addition, the higher risk specifcally of the microvascular complication of retinopathy, as demonstrated here in youth with potentially undiagnosed CD and in adults with CD and type 1 diabetes [11,35], remains undetermined. A potential contributing factor specifcally for retinopathy, however, may be reduced vitamin A levels secondary to malabsorption in the setting of CD [39]. Vitamin A plays an important role in the retina [40] and malnutrition retinopathy has been described in CD [39], although this warrants further investigation.…”
Section: Discussionmentioning
confidence: 97%